EULAR recommendations for the management of Behçet disease. Issue 12 (31st January 2008) - Hatemi, G; Silman, A; Bang, D; Bodaghi, B; Chamberlain, A M; Gul, A; Houman, M H; Kötter, I; Olivieri, I; Salvarani, C; Sfikakis, P P; Siva, A; et al.
Abstract : Objectives: To develop evidence-based European League Against Rheumatism (EULAR) recommendations for the management of Behçet disease (BD) supplemented where necessary by expert opinion. Methods: The multidisciplinary expert committee, a task force of the EULAR Standing Committee for Clinical Affairs (ESCCA), consisted of nine rheumatologists (one who was also a clinical epidemiologist and one also a Rehabilitation Medicine doctor), three ophthalmologists, one internist, one dermatologist and one neurologist, representing six European countries plus Tunisia and Korea. A patient representative was also present. Problem areas and related keywords for systematic literature research were identified. Systematic literature research was performed using Medline and the Cochrane Library databases from 1966 through to December 2006. A total of 40 initial statements were generated based on the systematic literature research. These yielded the final recommendations developed from two blind Delphi rounds of voting. Results: Nine recommendations were developed for the management of different aspects of BD. The strength of each recommendation was determined by the level of evidence and the experts' opinions. The level of agreement for each recommendation was determined using a visual analogue scale for the whole committee and for each individual aspect by the subgroups, who consider themselves experts in that field of BD. There was excellent concordance between the level of agreement of the whole group and the "experts in the field". Conclusion: Recommendations related to the eye, skin–mucosa disease and arthritis are mainly evidence based, but recommendations on vascular disease, neurological and gastrointestinal involvement are based largely on expert opinion and uncontrolled evidence from open trials and observational studies. The need for further properly designed controlled clinical trials is apparent.